Optimization of phosphoric acid treatment biochar using response surface method - Norazman, Farhaneem; Dimin @ Mohd Amin, Mohd Fairuz; Shaaban, Azizah; Mohamad, Noraiham (Penerbit Universiti Teknikal Malaysia Melaka, 2017)
Biochar is derived from the crop residue as a multifunctional materials for agricultural applications and as a soil enhancer to improve soil fertility. The physical and chemical properties of biochar are improved via phosphoric acid treatment. The aim of this study is to optimize the acid treatment of biochar for two factor; 1) concentration of phosphoric acid and 2) heating temperature via Response Surface Methodology (RSM) by using Design Expert 10 software. A set of 11 experiments were carried out based on Central Composite Design (CCD) with three repetitions at center point. Hence, the responses were set in two factors; 1) pH and 2) negative surface charge. The biochar produced from slow pyrolysis process of rubber wood sawdust (RWSD) in a horizontal tube furnace heated at 5⁰C/minute from room temperature to maximum temperature of 400⁰C with holding time of 1 hour. Characterization of treated biochar was performed using Scanning Electron Microscopy (SEM) and SEM with EDX. Analysis of variance of the pH and negative surface charge indicated that the selected quartic model was significant with p-value of <0.05. Predicted parameters to obtain the maximum negative surface charge were 1 Mol of acid concentration and 85⁰C of heating temperature with desirability of 98%.